Value propositions of chiropractic specialties: a national survey of regulators and specialists, informed by practicing chiropractors in Ontario and Quebec. - Hains, François; Blanchette, Marc-André (Journal of the Canadian Chiropractic Association, 2026)
Background: Canadian chiropractic specialties have evolved over five decades with varied provincial recognition. This study assesses how regulators, specialists, and chiropractors perceive the value and future development of chiropractic specialties. Methods: We conducted a bilingual, cross-sectional online survey. Respondents rated agreement with 12 value propositions (5-point Likert), and open-ended comments were analyzed thematically. Results: 248 respondents completed our survey (response rate of 5%): 12 regulators from 9 provinces, 58 specialists from 7 provinces, and 178 chiropractors from Ontario and Quebec. Agreement was consistently high (58.5--91.1%), with no significant differences between groups (F=1.85, p=0.160). Top future priorities: Paediatrics and Neurology (71%), Chronic Pain Management (65%), Geriatrics (56%). Qualitative analysis identified barriers (limited recognition, restricted scope, underutilization) alongside strong support for specialization. Conclusion: Despite reported consensus on specialization's value among respondents, structural barriers appear to limit integration within the healthcare system. Proposed solutions for advancing chiropractic specialties included national accreditation standards for postgraduate specialty programs, harmonized provincial recognition, and strengthened visibility.